Nibor, Libor and Euribor - all IBORs, but different - Arne Kloster; Olav Syrstad (Norges Bank, 2019)
This memo takes a closer look at what lays behind different benchmark interest rates. Particular emphasis is put on how the different practices for quotation can explain why Nibor's risk premium has on average been higher than the premiums in USD Libor and Euribor.
hdl:11250/2592985
Keywords: 330; IBOR; FX swaps; benchmark rates; risk premia; money market